Porter Generic Model Strategy for Micro, Small and Medium Enterprises (MSMs) in Dealing with ASEAN Economic Community (AEC) – (Case Study Deli Serdang Regency, North Sumatra –Indonesia) - Julita Julita, S.E., M.Si; Nel Arianty Nel Arianty, S.E., M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Indonesia has entered a new phase with partners in the neighboring countries, especially ASEAN members, namely ASEAN Economic Community (AEC) on December 31, 2015. One of the main pillars of AEC is free flow of goods, trade in goods in 2015 is conducted freely without barriers, both tariff and non-tariff. AEC implement schemes Common Effective Preferential Tariff (CEPT) that have previously been applied when the ASEAN Free Trade Area (AFTA), namely gradual tariff reductions made for certain types of goods carried in the timeframe that has been agreed. This study aims to find out the problems that often hinder the development of SMEs in Deli Serdang Regency in competitive advantage, especially in the face of the AEC, it is necessary for the existence of a strategy to create competitive advantage in the era of AEC. Many strategies to create competitive advantage and one generic strategy Porter. This strategy gives success in the company so that researchers want to adopt Porter generic strategies for MSMEs, especially in Deli Serdang. Objects in this study is micro, small and medium enterprises in the district of Deli Serdang. Data collection techniques using questionnaires and interviews / structured interviews and data analysis techniques using descriptive analysis techniques. The results showed that the strategy porter through indicators five forces porter that include competition among similar companies, the threat of new entrants, the threat of substitute products, bargaining power of buyers and bargaining power of suppliers is still included in the category enough or moderate, it indicates the presence of obstacles or problems faced by SMEs in Deli Serdang. Besides indicators porter five forces, the addition of the supporting indicators of the ability of innovation and technology as well as the government's attention is also included in the category enough or moderate, it indicates that the supporting indicators are still facing obstacles or problems.